DESIGN, CONSTRUCTION, AND TESTS OF TESLA TURBINE PROTOTYPE AS A TURBINE OF TOTAL FLOW SYSTEM IN GEOTHERMAL POWER PLANT - ADI PRANANTO (NIM : 131 06 030); Dosen Pembimbing : Prof. Dr. Ir. T.A. Fauzi Soelaiman, MSM, LUKMAN
One system that is still being developed for Geothermal Power Plant is the total flow system. In this system, the number of geothermal utilities are minimized. This system needs a turbine that can operate in two-phase fluids and fluids that have a lot of impurities. Total flow system usually requires lower investment costs, cheaper than other geothermal systems. Tesla Turbine was patented by Sir Nikola Tesla in 1913. It has several different characteristics from common steam turbine since it doesnÃ‚Â’t use blades to convert kinetic energy from fluid to mechanical energy. To convert the energy, Tesla Turbine uses parallel discs that are placed on a single shaft. These discs will rotate due to the adhesive force and fluid's viscosity. Tesla Turbine has an ability to work in two-phase fluids, therefore it is expected to work as a total flow system in a geothermal power plant. This final project covers the simulation and design of the Tesla Turbine's prototype. Modelling was carried out using FLUENT and GAMBIT softwares. Validation was done by comparing the results to previous simulations. Modelling was also conducted to analyze the phenomenon of fluid flow that occured in a Tesla Turbine. From the modelling, design is performed using Autodesk Inventor 2010. Dimensions of design is taken from a pre-existing test. Once the design was completed, manufacturing and assembly of the turbine were performed. This final project also analyze the results of prototipe testing. Tests carried out to see the energy conversion of Tesla Turbine, and measure the output power from the turbine using the alternator. Working fluid that will be used in this tests is lubricants oil. Flow rate of the lubricants oil is 2.8 kg/s. Rotational speed of the turbine is around 60 rpm. The rotational speed is too slow, so the alternator produced no power. Minimun rotational speed for the alternator to produce power is 150 rpm.